Beyond Affordability: Trust, Sustainability, and the Lived Experiences of Jan Aushadhi Kendra Owners (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study examines the lived experiences of Jan Aushadhi Kendra (JAK) owners to understand how the Pradhan Mantri Bhartiya Jan Aushadhi Pariyojana (PMBJP) is enacted at the grassroots level and what factors shape its long-term sustainability. Positioned at the intersection of entrepreneurship and public health delivery, JAK owners play a critical role in translating policy intent into everyday access to affordable medicines. Using a qualitative research design, in-depth semi-structured interviews were conducted with 74 JAK owners across Kerala and Karnataka. Data collection continued until thematic saturation was achieved, and the interviews were analysed using reflexive thematic analysis following Braun and Clarke's framework. The findings reveal four interrelated themes. First, owners articulated a social mission and hybrid entrepreneurial identity, framing their participation as public service-oriented rather than profit-driven. Second, the medical community emerged as institutional gatekeepers of trust, with limited endorsement from doctors and allied health professionals constraining consumer confidence in generic medicines. Third, business sustainability was found to be fragile, shaped by low margins, expiry-related losses, supply chain disruptions, and stock-outs that undermined both financial viability and customer trust. Finally, trust-building, consumer perceptions, and awareness gaps highlighted how persistent quality–price misconceptions and weak institutional communication compelled owners to act as informal educators, relying heavily on interpersonal relationships and word of mouth to sustain demand. Overall, the study demonstrates that while PMBJP has been effective in improving affordability, its sustainability depends on factors extending beyond price, including institutional trust, operational reliability, and coordinated communication. Strengthening medical endorsement, improving supply chain stability, and embedding systematic awareness initiatives are essential for positioning generic medicines as a trusted and mainstream component of India's healthcare system.